STUDENTS’ ABILITY IN THE TOEFL–LIKE STRUCTURE SUBTEST (A Study at STKIP PGRI of West Sumatera ) (Universitas PGRI Sumatera Barat, 2013)
Structure subtest is a student’s problem of English Department of STKIP PGRI in solving the TOEFL test. Based on data from the English Department graduated student, it is found that the result from the test scores is far from expectation. It is difficult for students to determine the use of any particular of speech in a sentence. This research aims to identify the structure of third year student ability of English Department of STKIP PGRI West Sumatra on every variable that exists on the TOEFL test, particularly the grammar part. Results of the study show that statistically their ability is at unsatisfactory levels. Nearly half of the research subjects (42.30%) is at a low level. Thus, it can be concluded that the ability of students in grammar TOEFL test is still low.